Is the Market Moral? Protestant Assessments of Market Society - Steensland, Brian (Review of religious research, 2011)
Is the market moral? Do different Protestant traditions have competing views of “market society”? Despite the increasing diffusion of market logics in American society, scholars of religion have little empirical data on these questions. Employing discourse analysis of market-related topics in two prominent Christian periodicals over a twenty-year period, this paper compares evangelical and mainline Protestant evaluations of markets. We find that neither group views markets as redeeming, self-regulating, or value neutral, and both groups argue that markets require constraints. Evangelicals prioritize moral constraints on markets, while mainline Protestants prioritize governmental and democratic constraints. The degree of difference between the groups varies considerably by topic, however, depending on the degree of potential state intervention. We close by discussing our findings in light of recent debates over the relationship between religious conservatism and economic conservatism. We find that economic conservatism among evangelicals is driven at least as much by a commitment to collective voluntarism as by atomized individualism or free market ideology.